2021
DOI: 10.1097/nna.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Leaders Employ Contemplative Practices to Promote Healthcare Professional Well-being and Decrease Anxiety

Abstract: OBJECTIVE The purpose of this study was to test the effectiveness of a daylong resilience retreat on healthcare professionals' anxiety levels, intention to engage in mindfulness practices, and self-efficacy around mindfulness. BACKGROUND Caregiver burnout is a concern that needs to be addressed at the organizational level so that professionals can reduce their risk of psychological injury while providing high-quality care. The COVID-19 (novel coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…Supporting our suggestions, Cunninghan and Cayir evaluated the impact of brief resilience retreats on healthcare workers’ anxiety during the COVID-19 pandemic and reported reductions in anxiety scores among nurses. In this study, nurse leadership achieved well-being among nurses by offering 10 daylong retreats that promoted mindfulness practices ( Cunningham & Çayir, 2021 ). Because greater emotional and psychological impact has been observed in professionals with less experience and younger nurses, measures to manage the impact of the COVID-19 pandemic should be reinforced in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our suggestions, Cunninghan and Cayir evaluated the impact of brief resilience retreats on healthcare workers’ anxiety during the COVID-19 pandemic and reported reductions in anxiety scores among nurses. In this study, nurse leadership achieved well-being among nurses by offering 10 daylong retreats that promoted mindfulness practices ( Cunningham & Çayir, 2021 ). Because greater emotional and psychological impact has been observed in professionals with less experience and younger nurses, measures to manage the impact of the COVID-19 pandemic should be reinforced in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…The result broadens our understanding of workplace wellbeing from the perspective of career support. In addition, although past studies have established associations between supporting variables and healthcare workers' wellbeing [19,20], this study explains why this may be the case by drawing attention to career commitment as a linking mechanism. Prior study has suggested that supervisory support can promote employees' career management [67].…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…Since leaders are generally viewed as agents of organizations, leadership styles and behaviors will have a great influence on their subordinates' emotional experience and psychological status and affect their wellbeing [17,18]. Although the existing research has examined the impact of supervisory support on healthcare workers' wellbeing [19,20], we know relatively little about the effects of career support variables on workplace wellbeing. Past research has linked perceived career support to attitudinal variables such as affective commitment [21], intention to leave [22], and work engagement [23].…”
Section: Introductionmentioning
confidence: 99%
“…Siendo favorable educar al personal de enfermería para que afronte los problemas psicológicos con naturalidad y con apoyo medico 10 . 11 generaron acciones contemplativas y de relajación para minimizar el impacto negativo emocional.…”
Section: Resultsunclassified